Immigration in U.S. history - Bankston, Carl L. (Carl Leon), 1952-; Hidalgo, Danielle Antoinette (Magill's choice., 2006)
This book "places special emphasis on the many ethnic communities that have provided American immigrants. For example, readers will find 17 articles treating African Americans; 56 articles about Asian immigrants, including articles specifically on Chinese, Filipino, Hmong, Japanese, Korean, Pacific Islander, South Asian, Southeast Asian, Tibetan, and Vietnamese immigrants; 25 articles on Latino and West Indian immigrants, including articles specifically on Cubans, Dominicans, Haitians, Jamaicans, and Mexicans; 10 articles on Middle Eastern immigrants, including articles specifically on Arabs, Iranians, and Israelis; 37 articles on European immigrants, including articles on German, Irish, Italian, Jewish, Polish, Russian, and Scandinavian immigrants."